Pengaruh Karakter Wirausaha, Minat Berwirausaha dan Lingkungan Keluarga Terhadap Aktivitas Berwirausaha Mahasiswa Universitas Negeri Padang - Fadilla Ulfah; Agus Irianto (Jurnal Ecogen, 2020)
The research aims to identify and analysis the effect of Entrepreneuship  character, Entrepreneurhip interest and family environment on student Entrepreneurhip  activity in Universitas Negeri Padang. The population in the research were qualifying for pass funded PKM-K and PMW 2018 in Universitas Negeri Padang. The analytical method used is path analysis using the SPSS version 21 program. The result show that 1) entrepreneurship character have a significant effect on entrepreneurial interest of student in Universitas Negeri Padang (62,4%.) 2) The family environment have a significant effect on entrepreneurial interest of students in Universitas Negeri Padang (39,1%). 3) entrepreneurship character have a significant effect on entrepreneurial activity of student in Universitas Negeri Padang (61,9%). 4) The family environment have a significant effect on entrepreneurial activity of students in Universitas Negeri Padang (41,1%). 5) Interest in entrepreneurship has a significant negative effect on student entrepreneurial activity at Universitas Negeri Padang (-39,5%).Keywords: entrepreneurship character, entrepreneurship interest, family environment, entrepreneurship activity